Pathogenicity of a TW-Like Strain of Infectious Bronchitis Virus and Evaluation of the Protection Induced against It by a QX-Like Strain - Yan, Shi-hong; Chen, Yang; Zhao, Jing; Xu, Gang; Zhao, Ye; Zhang, Guo-zhong (Frontiers in Microbiology, 2016)
Avian infectious bronchitis (IB), a highly contagious disease caused by avian infectious bronchitis virus (IBV), is of considerable economic importance to the poultry industry. New IBV TW-like strains have increasingly emerged in China in recent years; hence, evaluating their pathogenicity and developing a specific vaccine to guard against their potential threat to the poultry industry is important. Here, we examined the pathogenicity of a TW-like IBV strain (GD), and evaluated the protective efficacy of the QX-like strain (JS) against GD in challenge infections in chickens. The results revealed that strain-GD-infected birds experienced severe respiratory signs, renal lesions, and 30%–40% mortality. The GD virus had extensive tissue tropism, especially in the trachea, lungs, kidneys, and bursa of Fabricius, and was continuously shed via the respiratory tract and cloaca. The QX-like IBV strain JS is able to completely protect chickens from challenge with the TW-like IBV GD field strain, with no clinical signs or gross lesions, decreased tissue replication rates, lower ciliostasis score and reduced virus shedding. These findings indicate that IBV GD is highly virulent, and that QX-like JS may serve as an effective vaccine against the threat posed by IBV TW-like viruses.